(untitled) (UMRAN - Journal of Islamic and Civilizational Studies, 2016)
In both substantive and procedural rules, Islamic law enshrines a comprehensive legal framework that regulates the family system for the realisation of a sustainable justice for all parties to Islamic marriage institution. The basis of the philosophy of Islamic family law is that both husband and wife shall live together harmoniously, with mutual respect in order to produce an upright ummah, bearing rights and responsibilities towards one another. The husband, conferred with the privilege as head of the family and responsible for the wife, enjoys such favour within a limited sphere, to prevent ultra vires chances and abuses. The wife, ordained to bear the duty of followership and obedience towards the husband, is protected with judicial shield from darar which implies aggressive manners and ill treatment of irresponsible husbands. This paper critically examines these crucial issues pointing its sight on the classical texts, statutory provisions and the practical dispensation relating to the effect of darar on the wife and its judicial remedies with Bauchi state of Nigeria as case study. It is based on a qualitative research that employs both doctrinal and empirical research approach. The findings of the research reveal that the application of Islamic law in the Bauchi State Sharīʿah Courts has a number of challenges questioning the consistency of its practical aspect with the theoretical aspect; namely, the classical textual provisions.